2017
DOI: 10.1007/s11701-017-0719-8
|View full text |Cite
|
Sign up to set email alerts
|

Can dehydrated human amnion/chorion membrane accelerate the return to potency after a nerve-sparing robotic-assisted radical prostatectomy? Propensity score-matched analysis

Abstract: The objective of this study is to determine if the use of dehydrated human amnion/chorion membrane (dHACM) allograft wrapped around the NVB during a robotic-assisted radical prostatectomy (RARP) accelerates the return to potency. 940 patients with preoperative SHIM >20 underwent RARP with some degree of bilateral NS. Of these, 235 patients underwent RARP, with bilateral placement of dHACM graft around the NVBs. They were matched in a 1:3 proportion with a similar group of patients (n = 705) who did not receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 22 publications
4
24
0
Order By: Relevance
“…The dHACM allograft wrap was recently examined in a series of n = 940 patients (preoperative SHIM > 20) who underwent robotic RP with bilateral nerve-sparing [151]. A total of n = 235 had bilateral dHACM placement and these were propensity matched in a 1:3 proportion to non-dHACM patients (n = 705).…”
Section: Amnion-chorion Membranementioning
confidence: 99%
“…The dHACM allograft wrap was recently examined in a series of n = 940 patients (preoperative SHIM > 20) who underwent robotic RP with bilateral nerve-sparing [151]. A total of n = 235 had bilateral dHACM placement and these were propensity matched in a 1:3 proportion to non-dHACM patients (n = 705).…”
Section: Amnion-chorion Membranementioning
confidence: 99%
“…dHACM group showed a short mean time to return to potency compared with the group of non-graft patients supporting the hypothesis that the application of dHACM is able to accelerate the return to potency. Furthermore, it has been demonstrated that the application of dHACM does not increase the risk of biochemical cancer recurrence (BCR) [91].…”
Section: Radical Prostatectomymentioning
confidence: 99%
“…In addition, a local inflammatory response is triggered, which causes the delay to reaching continence and potency. The inflammatory response triggers edema, acidosis, and apoptosis, which can potentially lead to nerve damage [10,11]. So far, there is no ideal strategy for preventing scar and adhesion formation in the nervous system.…”
Section: Introductionmentioning
confidence: 99%
“…So far, there is no ideal strategy for preventing scar and adhesion formation in the nervous system. Clinical benefit of growth and anti-inflammatory factors could be crucial for the regeneration of the neurovascular bundle (NVB) [11].…”
Section: Introductionmentioning
confidence: 99%